Under-utilised opportunity: key contribution of public health nurses and school health services for outreach in Delhi, India - Sood, Neerja (International Journal Of Community Medicine And Public Health, 2016)
Background: The post of Public Health Nurses (PHNs) was created and filled for the first time in Delhi Administration, in 1978-79 under School Health Scheme (SHS) to provide services to school children but overtime they were utilised in public health activities without changing their job profile. This paper presents a history of development of SHS in Delhi and the various roles that PHNs played through it and present a case study of SHS in Delhi. Methods: A systems approach was used to study SHS as a part of Directorate of Health Delhi. Purposively selected school health clinics in East and North East Districts managed by Government and NGOs were studied. Review of reports, observation and interview checklist were used. Results: PHNs in SHS provided comprehensive services to school children. Since end of 1988 they were diverted to various public health activities. SHS covered nearly 40-50 percent government schools with no further expansion. Staff was transferred / posted to new hospitals and districts during end of 1990s. In 2002-03 Non-Government Organisations (NGOs) were involved to cover schools but by end of 2010 many NGOs withdrew from scheme. Conclusions: Based on findings, this paper argues that, while PHNs played vital public health roles in the 1970s and 80s, policy changes in governance and service structures have diminished their role since late 1990s. Other options tried by government in 2000s, such as opening SHS to NGOs, have largely failed. The under-utilised potential of PHNs needs to be recognised and better deployed.